IMPLEMENTASI FLIPPED CLASSROOM MELALUI MEDIA VIDEO MICRO-LEARNING UNTUK MENINGKATKAN PERILAKU MENDUKUNG WAWASAN NUSANTARA PADA SISWA KELAS VIII SMPN 17 MALANG - M. Ma'rifani; Yulius Rustan Effendi; Muthomimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examined the effectiveness of implementing the Flipped Classroom model supported by micro-learning videos in fostering students' behavior aligned with the values of Wawasan Nusantara (the Indonesian Archipelagic Outlook). The research was motivated by the limited participation of students during Pancasila Education lessons, which contributed to inadequate conceptual understanding and weak internalization of national values. A collaborative Classroom Action Research (CAR) design based on the Kemmis and McTaggart spiral model was employed over two action cycles. The participants consisted of 32 eighth-grade students of SMPN 17 Malang during the second semester of the 2025/2026 academic year. Data were gathered through classroom participation observation sheets, pre-test and post-test assessments comprising 15 case-based multiple-choice questions, students' reflective journals, and supporting documentation. The collected data were analyzed using descriptive-comparative techniques and qualitative analysis involving data reduction, data display, and conclusion drawing. The intervention was considered successful when at least 75% of the students demonstrated active participation and a minimum classical learning mastery of 85% was achieved. The findings revealed continuous improvement across the two cycles. The proportion of actively participating students increased from 56.25% in Cycle I to 87.50% in Cycle II, while classical learning mastery improved from 65.63% to 90.63%. These results indicate that integrating the Flipped Classroom approach with micro-learning videos creates a more engaging learning environment, encourages active student participation, and strengthens the internalization of Wawasan Nusantara values within Pancasila Education.